2021
DOI: 10.1186/s13006-021-00421-0
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ and midwives’ perspectives on how the pursuit for the ‘perfect’ body image affects their own breastfeeding practices: a qualitative study in Ghana

Abstract: Background Body image concerns have been widely documented in the literature as one reason why most women shorten the breastfeeding duration of their infants. Negative body image concerns among breastfeeding mothers may lead to depressive symptoms. There is a paucity of literature on how body image affects the breastfeeding practices of nurses and midwives. Therefore, this study explored the perspectives of breastfeeding nurses and midwives on how their body image affected their breastfeeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
1
6
0
1
Order By: Relevance
“…This could explain the findings in the current results that women who breastfeed are less concerned about the appearance of their body compared to women who viewed their bodies more aesthetically. Furthermore, the findings of Acheampong and Abukari (2021) were also in line with the present findings since their research results suggested that there were concerns surrounding weight gain and its impact on body image which was also mirrored in the current research findings that women engaged in more exercise to regain their pre-pregnancy body. In addition, Swanson et al (2017) suggested that body image scores were lower in obese women, suggesting that obesity negatively affects breastfeeding initiation and maintenance.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This could explain the findings in the current results that women who breastfeed are less concerned about the appearance of their body compared to women who viewed their bodies more aesthetically. Furthermore, the findings of Acheampong and Abukari (2021) were also in line with the present findings since their research results suggested that there were concerns surrounding weight gain and its impact on body image which was also mirrored in the current research findings that women engaged in more exercise to regain their pre-pregnancy body. In addition, Swanson et al (2017) suggested that body image scores were lower in obese women, suggesting that obesity negatively affects breastfeeding initiation and maintenance.…”
Section: Discussionsupporting
confidence: 89%
“…There has also been some previous qualitative work, for example Acheampong and Abukari (2021) found that after interviewing 25 breastfeeding nurses and midwives in Ghana with infants younger than two, many had body image worries influenced by concerns surrounding generalised weight gain, which was attributed to eating extra food to maintain a healthy milk supply. Another qualitative study was carried out by Fern et al (2014) who conducted email interviews with 40 women who were allocated to three groups; currently breastfeeding, former breastfeeding or bottle-feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, contrasting evidence was present in the literature, with at least one study describing a higher likelihood of initiating breastfeeding when mothers experienced higher weight concerns [ 89 ], and a higher prevalence of body dissatisfaction and eating behaviors in obese mothers, who were in turn more likely to maintain exclusive breastfeeding or postpone weaning [ 90 ]. This finding might be interpreted in light of cultural factors, as contrasting evidence was offered by two studies conducted in Europe—Norway and Italy [ 89 , 90 ]—in comparison to the rest of the world—predominantly English-speaking: United States, United Kingdom, Nigeria, and Australia [ 39 , 79 , 86 88 , 91 ].…”
Section: Resultsmentioning
confidence: 96%
“…Partner influences were described to influence body image preoccupations, thin-ideal internalization and consequently breastfeeding self-efficacy [ 84 , 85 ], which in turn has consistently reported predicting the likelihood of breastfeeding itself [ 86 , 87 ]. The social discomfort of breastfeeding in public has been repeatedly reported as an inhibitor to its adoption, and obese women were significantly more likely to report social discomfort [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
“…Participants also expressed concern about the possibility of their breasts sagging for them to become unattractive if they practiced exclusive breastfeeding. Sagging breast as a deterrent for optimal breastfeeding has been reported widely in literature to an extent that, even lactating nurses and midwives also have concerns about their breast sagging after breastfeeding [ 54 – 57 ]. With this information, antenatal education should persistently be tailored to address body image issues.…”
Section: Discussionmentioning
confidence: 99%